Promoting Gender Equality - Johanna Niemi (Springer, 2022)
The article discusses the Nordic legal feminism in the light of the phases of feminist theory. Nordic gender equality policy and law have been integrated with the welfare state, promoting general equality. All Nordic countries have ascribed to strategic equality policies, however, with somewhat different vigour. In all these countries gender equality laws have been assigned an active role in promoting equality and preventing discrimination. Lately, research in law and gender has turned to theory and gender and sex are seen as socially constructed through legal discourses and practices in all fields of law. The chapter argues that different feminist approaches are still relevant for the analysis of law.
Nordic Law in European Context